2014
DOI: 10.4097/kjae.2014.66.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Antiemetic effect of propofol administered at the end of surgery in laparoscopic assisted vaginal hysterectomy

Abstract: BackgroundPostoperative nausea and vomiting (PONV) commonly occur after general anesthesia, especially in women. In this study, we evaluated the antiemetic efficacy of propofol administered at the end of surgery in highly susceptible patients undergoing a laparoscopy-assisted vaginal hysterectomy.MethodsA total of 107 women undergoing a laparoscopy-assisted vaginal hysterectomy under general anesthesia were enrolled for this prospective, double-blind, randomized study. Fifteen minutes before the end of surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…However, there is no correlation between CYP activity and BMI [50]. The pharmacokinetics of propofol, which is frequently used for anesthesia induction, are not affected by obesity [42]; moreover, propofol has antiemetic activity [56].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no correlation between CYP activity and BMI [50]. The pharmacokinetics of propofol, which is frequently used for anesthesia induction, are not affected by obesity [42]; moreover, propofol has antiemetic activity [56].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Song et al [16] it was demonstrated that propofol given after sevoflurane and desflurane anesthesia for outpatient laparoscopic cholecystectomy significantly decreased the incidence of PONV compared with control. Similarly, reports suggest that low-dose of propofol (0.5 or 1 mg/kg) administration at the end of surgery effectively reduce the incidence of PONV within 2 h postoperatively in highly susceptible women undergoing a laparoscopy-assisted vaginal hysterectomy and receiving opioid-based PCA [21]. In this present study, it was realized that 105 (91.30%) from the propofol group experienced no incidence of PONV compared with 7 (6.09%) parturient from the control group, a similar observation Chatterjee et al [22], Apfel et al [23] and Warltier et al [24] have also earlier submitted.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the included trials contain differences that could potentially influence outcomes. Propofol has been reported to have anti-emetic properties (5,32), and propofol combined with volatile anesthesia is related to lower PON incidence (33). Some data from the included studies used propofol as an anesthetic method.…”
Section: Discussionmentioning
confidence: 99%